2023
DOI: 10.3390/ph16050708
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Potential and Bioactive Profiles of Piper sarmentosum Ethanolic Extract-Treated Stem Cells

Abstract: Piper sarmentosum is a well-known traditional herbal plant in various diseases treatments. Multiple scientific studies have also reported various biological activities exhibited by the plant’s extract, such as antimicrobial, anticarcinogenic and antihyperglycemic activities, and, in addition, a bone protective effect in ovariectomized rats has been reported. However, no known Piper sarmentosum extract is involved in osteoblast differentiation using stem cells. Our study aims to identify the potential of P. sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…A total of 14 articles related to the morphological approach, published between 2013 and 2023 were selected. The human cultured stem cells used for the in-vitro studies include both peripheral blood mononuclear cells (PBMSC) ( Kleinhans et al, 2015 ; Maria et al, 2018 ; Steller et al, 2020 ; Grünherz et al., 2020 ; Zainol Abidin et al., 2023 ) and mesenchymal stem cells (MSc) involved 5 studies ( Maria et al, 2017 ; Hashimoto et al, 2018 ; Liu et al, 2018 ; Ganguly et al, 2020 ; Nugraha et al, 2023 ) whereas periodontal ligament stem cells (PDLSC) ( Di Vito et al, 2020 ; Frasheri et al, 2023 ) and dental pulp stem cells (DPSC) ( Escobar et al, 2020 ; Escobar et al, 2023 ) involved two studies ( Table 3 ). The outcomes of the risk of bias assessment in Table 4 reflect the quality assessment analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 articles related to the morphological approach, published between 2013 and 2023 were selected. The human cultured stem cells used for the in-vitro studies include both peripheral blood mononuclear cells (PBMSC) ( Kleinhans et al, 2015 ; Maria et al, 2018 ; Steller et al, 2020 ; Grünherz et al., 2020 ; Zainol Abidin et al., 2023 ) and mesenchymal stem cells (MSc) involved 5 studies ( Maria et al, 2017 ; Hashimoto et al, 2018 ; Liu et al, 2018 ; Ganguly et al, 2020 ; Nugraha et al, 2023 ) whereas periodontal ligament stem cells (PDLSC) ( Di Vito et al, 2020 ; Frasheri et al, 2023 ) and dental pulp stem cells (DPSC) ( Escobar et al, 2020 ; Escobar et al, 2023 ) involved two studies ( Table 3 ). The outcomes of the risk of bias assessment in Table 4 reflect the quality assessment analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies focus solely on the staining of osteoblast differentiation ( Escobar et al, 2020 ; Escobar et al, 2023 ; Ganguly et al, 2020 ; Di Vito et al, 2020 ; Frasheri et al, 2023 ; Zainol Abidin et al., 2023 ; Nugraha et al, 2023 ), three studies only on morphological evaluation methods for osteoclast differentiation ( Kleinhans et al, 2015 ; Steller et al, 2020 ; Grünherz et al., 2020 ) and another four articles involved qualification analysis of both osteoblast and osteoclast differentiation ( Hashimoto et al, 2018 ; Maria et al, 2018 ; Liu et al, 2018 ) ( Table 3 ). All the staining techniques were proven to be successful in evaluating the presence of osteoblast and osteoclast differentiation in cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In The antioxidant and anticancer properties of the methanolic extract of P. sarmentosum can be attributed to the synergistic effects of its diverse array of compounds. Phenolic compounds, flavonoids, alkaloids, and terpenoids such as myricetin, quercetin, apigenin, naringenin, rutin and vitexin, collectively contribute to the observed effects, highlighting the potential of this natural extract as a source of bioactive compounds with therapeutic implications (Ismail et al, 2018;Zainol Abidin et al, 2023). The relationship between the total phenolic content, antioxidant activity, and…”
Section: Cytotoxic Activity Of P Sarmentosum Methanolic Extract Again...mentioning
confidence: 97%
“…The leaves and aerial parts of the plant have been particularly significant in these compound discoveries. Several pharmacological agents, including antiosteoporosis ( Suhana Mohd Ramli et al, 2012 ; Ekeuku et al, 2023 ; Zainol Abidin et al, 2023 ), anti-inflammatory agents ( Zakaria et al, 2010 ; Makchuchit et al, 2017 ; Akmal et al, 2022 ), antioxidants ( Ugusman et al, 2011 ; Wang et al, 2017 ), antimalarial agents ( Najib Nik A Rahman et al, 1999 ), antimicrobial agents ( Masuda et al, 1991 ), antihypertensive agents ( Mohd Zainudin et al, 2015 ; Othman et al, 2022 ), antidiabetic agents ( Othman et al, 2022 ; Nguyen et al, 2023 ), anticancer agents ( Zainal Ariffin et al, 2009 ; Hematpoor et al, 2018 ) and neuroprotective ( Ridtitid et al, 1998 ; Yeo et al, 2018 )agents, have been found.…”
Section: Introductionmentioning
confidence: 99%